Theories and limitations of EU-friendly interpretation of the Polish Constitution - Kos, Katarzyna (Polish Review of International and European Law, 2023)
The article concerns the issue of theories and limitations of EU-friendly interpretation of the Polish Constitution. It discusses two theories, which are a basis for this method of interpretation of the Constitution: “theory of the multicentricity of legal systems” and “theory of the Europeanisation of the Constitution”. The author notices that both of them focus on legal interpretations but do not satisfactorily explain the basis of the growing impact of EU law on understanding constitutional regulations. They propose some thesis concerning legal interpretations that are implied from observing reality and they attempt to indicate the necessity for EU-friendly interpretations of the Constitution. Thus, it is significant to formulate frames for applying this method of interpretation. The article systematizes limits of EU-friendly interpretation of the Constitution, particularly concentrating on the prohibition of contra legem interpretation, prohibition of interference in the “constitutional identity” and guarantee of a higher standard of system of human rights. There are also considered problems that result from these limitations.